Mycobacterium avium Complex Cutaneous Infections in Non-HIV Patients: Case Report and Literature Review. Issue 6 (November 2018) - Rizvi, Humaira; Saravolatz, Louis Donald
Abstract : Abstract: We report a rare case of Mycobacterium avium complex cutaneous infection in a non-HIV patient with a report of 13 other cases of M. avium complex cutaneous infection in non-HIV patients found in the literature since 1992.